Pembuatan Kerajinan Tangan Keset Dari Barang Bekas Untuk Meningkatkan Keberhasilan Pengajaran Seni Budaya Dan Prakarya - Putra, Thoha (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
Creativity is an important aspect for every student in making handicrafts, and the level of creativity possessed by students will greatly influence their learning achievement. Arts and Culture and Crafts Education (SBdP) in elementary schools functions to develop students' skills as preparation for creating work as well as developing a sense of beauty and the ability to appreciate the arts and crafts skills in elementary schools and their application in the classroom. The students' skills and creativity depend on the teacher's ability to transfer the knowledge they have to their students. This community service activity aims to provide training to teachers to be able to process used goods into beautiful and useful items. The target of this activity is that teachers are able to create used goods into good handicrafts that have high economic value.